Heme-Oxygenase-1 Is Decreased in Circulating Monocytes and Is Associated With Impaired Phagocytosis and ROS Production in Lupus Nephritis - Cuitino, Loreto; Obreque, Javiera; Gajardo-Meneses, Patricia; Villarroel, Alejandra; Crisóstomo, Natalia; San Francisco, Ignacio F.; Valenzuela, Rodrigo A.; Méndez, Gonzalo P.; Llanos, Carolina (Frontiers in Immunology, 2019)
Lupus nephritis (LN) is one of the most serious manifestations of systemic lupus erythematosus (SLE). Based on studies showing the potential role of heme oxygenase-1 (HO-1), an enzyme that catalyzes the degradation of heme and has anti-inflammatory properties in SLE development, we decided to explore HO-1 in LN. Accordingly, we evaluated HO-1 levels and function in circulating and infiltrating monocytes and neutrophils of LN patients. HO-1 levels were assessed in peripheral monocytes of LN patients and controls by flow cytometry and immunofluorescence microscopy. Phagocytosis and the production of ROS were evaluated to determine the effect of HO-1 in monocytes function. In addition, renal biopsies with proliferative LN were used to identify HO-1 in infiltrating cells and renal tissue by immunofluorescence and immunohistochemistry. Biopsies of HC and patients that underwent nephrectomy were included as controls. Circulating pro-inflammatory monocytes and activated neutrophils were increased in LN patients. HO-1 levels were decreased in all subsets of monocytes and in activated neutrophils. LN monocytes showed increased phagocytosis and higher production of ROS than HC. When HO-1 was induced, phagocytosis and ROS levels became similar to those of HC. HO-1 was mostly expressed in renal tubular epithelial cells (RTEC). Renal tissue of LN patients showed lower levels of HO-1 than HC and while infiltrating immune cells of LN showed lower levels of HO-1 than biopsies of patients that had renal surgery. HO-1 is decreased in circulating monocytes and activated neutrophils of LN patients. HO-1 levels modulate the phagocytosis of LN monocytes and ROS production. HO-1 expression in RTEC might be an attempt of self-protection from inflammation.